Unveiling the mechanisms of how cationic polyacrylamide affects short-chain fatty acids accumulation during long-term anaerobic fermentation of waste activated sludge - Liu, Xuran; Xu, Qiuxiang; Wang, Dongbo; Wu, Yanxin; Yang, Qi; Liu, Yiwen; Wang, Qilin; Li, Xiaoming; Li, Hailong; Zeng, Guangming; Yang, Guojing (Water research (Oxford), 2019)
Cationic polyacrylamide, a flocculation powder widely used in wastewater pretreatment and sludge dewatering, was highly accumulated in waste activated sludge. However, its effect on short-chain fatty acids (SCFAs) accumulation from anaerobic fermentation of waste activated sludge has not been investigated. This work therefore aims to deeply unveil how cationic polyacrylamide affects SCFAs production, through both long-term and batch tests using either real waste activated sludge or synthetic wastewaters as fermentation substrates. Experimental results showed that the presence of cationic polyacrylamide not only significantly decreased the accumulation of SCFAs but also affected the composition of individual SCFA. The concentration of SCFAs decreased from 3374.7 to 2391.7 mg COD/L with cationic polyacrylamide level increasing from 0 to 12 g/kg of total suspended solids, whereas the corresponding percentage of acetic acid increased from 45.2% to 55.5%. The mechanism studies revealed that although cationic polyacrylamide could be partially degraded to produce SCFAs during anaerobic fermentation, cationic polyacrylamide and its major degradation metabolite, polyacrylic acid, inhibited all the sludge solubilization, hydrolysis, acidogenesis, acetogenesis and homoacetogenesis processes to some extents. As a result, the accumulation of SCFAs in the cationic polyacrylamide added systems decreased rather than increased. However, the inhibition to acetogenesis and homoacetogenesis was slighter than that to acidogenesis, leading to an increase of acetic acid to total SCFAs. It was further found that cationic polyacrylamide had stronger ability to adhere to protein molecules surface, which inhibited the bioconversion of proteins more severely. Illumina MiSeq sequencing analyses showed that cationic polyacrylamide decreased microbial community diversity, altered community structure and changed activities of key enzymes responsible for SCFAs accumulation. [Display omitted] •cPAM decreased the yield of SCFAs from anaerobic fermentation of WAS.•cPAM affected the composition of individual SCFA.•cPAM showed different inhibition on microbes involved in the anaerobic fermentation.•cPAM's degradation product polyacrylic acid also suppressed anaerobic fermentation.•cPAM decreased microbial community diversity and altered community structure.